2010
DOI: 10.1038/ajh.2009.228
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Prevents the Development of Pathological Cardiac Hypertrophy and Contractile Dysfunction in the SHR Without Lowering Blood Pressure

Abstract: Resveratrol treatment was beneficial in preventing the development of concentric hypertrophy and cardiac dysfunction in SHR. The cardioprotective effect of resveratrol in SHR may be partially mediated by a reduction in oxidative stress. Thus, resveratrol may have potential in preventing cardiac impairment in patients with essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
121
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 22 publications
15
121
0
2
Order By: Relevance
“…7,8) Although the compound tended to improve the whole cardiac and LV mass indexes, the effects were not significant. In contrast, "-viniferin significantly reduced SBP and cardiac mass in SHRs.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…7,8) Although the compound tended to improve the whole cardiac and LV mass indexes, the effects were not significant. In contrast, "-viniferin significantly reduced SBP and cardiac mass in SHRs.…”
Section: Discussionmentioning
confidence: 90%
“…The dose of resveratrol was chosen according to previous experimental models using hypertension in SHRs. 7,8) In order to give the same dose of the molecules, the dose of "-viniferin used was the double of that of the monomer. The untreated WKYs and SHRs were administered vehicle orally by gavage (corn oil, Sigma) for the same period.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, it has been demonstrated from both in vitro and in vivo studies to have cardioprotective effects, including anti-inflammatory, antioxidative, and anti-hyperlipidemic properties as well as the prevention of platelet aggregation and cardiac hypertrophy [12][13][14] . These beneficial effects of resveratrol may provide explanations for the "French paradox", the finding that the consumption of red wine is associated with a decreased incidence of cardiovascular diseases [15] .…”
Section: Introductionmentioning
confidence: 99%
“…These include the following: (i) hypertension (Liu et al 2005;Dolinsky et al 2009;Thandapilly et al 2010;Toklu et al 2010;Wojciechowski et al 2010;Chan et al 2011;Rimbaud et al 2011); (ii) obesity (Louis et al 2011;Qin et al 2012 (Barger et al 2008). There is also one study that reported cardioprotection in an animal model of heart failure (Tanno et al 2010).…”
mentioning
confidence: 99%